ANEMIC SYNDROME IN PATIENTS WITH CHRONIC HEART FAILURE - V. N. Larina; B. Ya. Bart; E. L. Balabanova (Российский кардиологический журнал)
The prevalence of anemia and its effects on chronic heart failure (CHF) course in ambulatory patients of various age were examined. The study included 282 patients (86 women, 196 men) with NYHA Functional Class (FC) II-II CHF, aged from 39 to 85 years (median age 67 [62-73] years). In CHF patients, anemia prevalence reached 18,8%, and in those aged over 60 years – 20,2%. The prevalence of anemia in elderly men (11%) and women (9,2%) was similar. There was no significant difference in anemia prevalence between elderly individuals with normal (21%) or reduced left ventricular ejection fraction, LVEF (19,3%). In elderly CHF individuals with renal dysfunction, anemia prevalence was as high as 36,9%. In the majority of participants, anemia was normocytic, while iron deficiency was observed in 36,9%, vitamin B12 deficiency – in 6,5%, and folic acid deficiency – in 10,9%. In 45,6% of the patients, anemia genesis was unclear. There was a strong association between anemic syndrome in CHF and age, creatinine clearance, diabetes mellitus, and the incidence of hospital admission due to CHF decompensation.